Cross-population tongue image features and tongue coating microbiome changes in the evolution of colorectal cancer - Liu, Fang; Su, Dan; Shi, Xing; Xu, Shu-min; Dong, Yu-kun; Li, Zhi; Cao, Bo; Ren, Dong-lin (Frontiers in Microbiology, 2025)
IntroductionTongue diagnosis, a cornerstone of Traditional Chinese Medicine (TCM), relies significantly on the assessment of tongue coating, which is used to evaluate Zang-fu organ functions, qi and blood dynamics, and the influence of pathogenic factors. This diagnostic method is integral to disease diagnosis and treatment in TCM. Recent research suggests a strong correlation between the characteristics of tongue coating and its microbial composition. These microbial variations may influence the formation and changes in tongue coating and are potentially linked to the progression of specific diseases. However, comprehensive research on the association between tongue coating, its microorganisms, and colorectal cancer (CRC) is limited. Notably, the quantitative aspects of tongue diagnosis and the microbial diversity in tongue coatings across different stages of colorectal cancer (from healthy individuals to colorectal adenoma (CRA) and CRC patients) are yet to be fully elucidated. By studying the cross-population characteristics of tongue image and tongue coating microorganisms during the evolution of colorectal cancer, the differences of tongue image characteristics and tongue coating microorganisms among different populations were further evaluated, providing references for early screening, diagnosis and treatment of colorectal cancer.MethodsThe tongue image features of the subjects were collected by DS01-B tongue surface information collection system, mainly including tongue quality and tongue coating, and the tongue image was quantitatively analyzed by color space Lab value. The microbial characteristics of tongue coating were detected by high-throughput sequencing (16SrRNA amplicon sequencing). All subjects came from the patients in the Sixth Affiliated Hospital of Sun Yat-sen University and recruited volunteers (divided into health group, CRA group and CRC group), and obtained the ethical approval of the Sixth Affiliated Hospital of Sun Yat-sen University (ethical batch number: 2021ZSLYEC-328).ResultsA total of 377 subjects were recruited in this study, including 56 healthy subjects, 65 colorectal adenomas and 256 colorectal cancer patients. The results showed that: in terms of texture of fur, the “thick fur” was a significant statistical difference (p < 0.05) in the 3 groups. In addition, there was also a statistical difference in “greasy fur” and “peeled fur” among the 3 groups (p < 0.05). Lab quantitative analysis of tongue color and fur color: The results showed that the L value of tongue color in healthy group was significantly different from that in CRA group and CRC group (p < 0.01), but there was no significant difference between CRA group and CRC group (p > 0.05). Tongue coating microorganisms, there was no significant difference in the richness and diversity of the three groups of subjects (p > 0.05). There were 296 species in the three groups, accounting for 44.65%, and the species in colorectal cancer population was the most, reaching 502. From the differences in community composition among the three groups, it was found that there were certain differences in bacterial community composition between healthy people, CRA and CRC, and the differences became more and more obvious with the development of the disease.ConclusionThis study revealed the specific cross-population tongue image characteristics and the specificity of tongue coating microorganisms in the evolution of CRC, providing new research ideas for early screening, early diagnosis, mechanism exploration, prevention and treatment of colorectal cancer.